2020
DOI: 10.3390/ijerph17249382
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of ‘Mild Lockdown’ in Japan during the COVID-19 Pandemic: A Nationwide Survey under a Declared State of Emergency

Abstract: This study examined the psychological distress caused by non-coercive lockdown (mild lockdown) in Japan. An online survey was conducted with 11,333 people (52.4% females; mean age = 46.3 ± 14.6 years, range = 18–89 years) during the mild lockdown in the seven prefectures most affected by COVID-19 infection. Over one-third (36.6%) of participants experienced mild-to-moderate psychological distress (Kessler Psychological Distress Scale [K6] score 5–12), while 11.5% reported serious psychological distress (K6 sco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(139 citation statements)
references
References 55 publications
6
118
2
1
Order By: Relevance
“…Excessive anxiety and depression may be symptoms of psychological distress. Previous studies have shown that people with a history of psychiatric disorders are more anxious and show greater psychological distress during the COVID-19 pandemic 21 . However, because it is easier to confirm feelings of worry than to make a psychiatric diagnosis, we believe that it is useful to identify the presence of worry among workers for determining health status.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive anxiety and depression may be symptoms of psychological distress. Previous studies have shown that people with a history of psychiatric disorders are more anxious and show greater psychological distress during the COVID-19 pandemic 21 . However, because it is easier to confirm feelings of worry than to make a psychiatric diagnosis, we believe that it is useful to identify the presence of worry among workers for determining health status.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness in old age is generally acknowledged as an urgent public health problem [ 44 ], particularly in those living without a spouse or partner. In turn, during the COVID-19 pandemic, loneliness was found to be associated with higher levels of psychological distress [ 12 ] and even with malnutrition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, people were encouraged to stay at home in relative isolation to prevent viral spread, and non-essential businesses were temporarily closed [ 3 ], leading to a sharp increase in unemployment rates internationally [ 4 ]. The restrictive social distancing policies and the general sense of uncertainty during the COVID-19 outbreak ultimately reduced contact between people and instigated a growing worldwide concern about increased loneliness [ 5 , 6 , 7 , 8 ] and more mental health problems in the general population [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, D oc could be high in Japan regardless of the testing kit and hospital bed availability if people fail to recognize the serious risks and are unwilling to be admitted to the hospital [ 36 ]. The general public in Japanese only became aware of the severity of the epidemic after a nationwide lockdown was initiated on 7 April [ 37 ], which is beyond the range of our data availability. Comparatively, the correlation reached 35% to 62% in India and China because the calculation begins from the date the cordon sanitaire was implemented.…”
Section: Discussionmentioning
confidence: 99%